Opportunity to strengthen public management at the regional or local authorities with the resources of specific budgetary GSP and SGR destination (2017)
In this document can be found as territorial entities, in the exercise of compliance with the essential fines of the state and especially for what is contemplated in the political letter of 1991, in its article 287, They must exercise the competences that correspond and are administered The taxes and the time that they participate of the national incomes. It is in this sense that an analysis is made of the main incomes received by the nation and appropriated in their budgets under the terms of Decree 111 of 1996 or organic statute of budget, Focusing on the municipalities in the revenues by the concept of general system of participations (SGP) and general system of royalties (SGR). Revenues that have had significant changes, and which allow the managers to make investments in several sectors with special supervision and subjection to the specific destination law. Noting the inefficiency and difficulty currently presented by the entities to process the royalties resources, and the risk of cuts in the GSP as it depends on the behavior of the economy. Thus, it is analyzed that a large part of the municipalities of the country are very dependent on these two resources at the 2015 cut, whereas the own resources, tax as a child tax on industry and commerce and land are important to ensure the sustainability of the regions. All of the above in a difficult situation for public administrators, and their challenge in improving the finances of the territories with several actors in the process and the political character of the state entities, the normativity, the high turnover of people in the organisms and the Lack of continuity to ensure the proper functioning and compliance with state territorial functions.